Two-dimensional gersiloxenes with tunable bandgap for photocatalytic H2 evolution and CO2 photoreduction to CO - Fulai Zhao (Nature Portfolio, 2020)
Solar energy conversion may provide a renewable means to store energy as fuels, although there are a limited range of suitable photocatalysts. Here authors develop germanium and silicon based 2D materials with tunable bandgaps for high-performance photocatalytic water and CO2 reduction.